Upaya Meningkatkan Pemahaman Siswa terhadap Perguruan Tinggi dengan Menggunakan Media Whatsapp melalui Bimbingan Kelompok pada Siswa Sekolah Menengah Kejuruan - Helmisah Helmisah (Mahesa Research Center, 2022)
This study aims to improve readiness to continue their studies to higher education through group guidance for class XI students of SMKN 3 Karang Baru. The approach used in this research is descriptive quantitative with the type of class action research (Class Action Research). This research model refers to Kemmis and McTaggart. The subjects of this study were 31 students in one virtual class. The object of this research is the readiness to continue their studies to university. Data collection methods used are scale, observation and interviews. The instruments used are the scale of readiness to continue their studies to college, observation guidelines and interview guidelines. The data analysis technique uses quantitative data tabulation based on the results of the action and is described in the form of sentences and concrete data. This research was carried out in one cycle with five stages of action, namely giving study program and college reference assignments, small group discussions, expository followed by class discussions, problem solving techniques and class discussions. The results of the study show that group guidance can increase readiness to continue their studies to college. This increase can be seen from the comparison of pre test results which show the medium readiness category with an average score of 30.41 and the post test results are in the high category with an average score of 37.90, an increase of 15.6% from the condition before the action was taken. The improvement can be seen from the results of observations and interviews with students which show an increase in students' ability to explain the reasons for choosing study programs and universities, increasing students' abilities in preparing activity schedules, increasing students' abilities in recognizing and formulating options for solving learning problems and improving aspects of learning. -other aspects of readiness.